PRINCIPLES FOR CONSTRUCTION OF TESTS IN STYLISTICS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article discusses the features and specifics of using interactive methods for testing foreign language teaching in higher educational institutions, which make it possible to make classes more diverse. The use of units of the Russian language and their practical use in various forms of speech, styles and genres of the literary language is considered expedient.Expediency of use in the process of teaching foreign languages when studying units of any level and focused on enhancing the creative thinking of students.